Συσχέτιση του ACAA2 γονιδίου με την γαλακτοπαραγωγή και κρεατοπαραγωγή του προβάτου της φυλής Χίου - Χατζησάββα, Αθηνά (Τμήμα Γεωπονικών Επιστημών, βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The sheep industry in Cyprus is growing. The main and most widely farmed sheep breed is the breed Chios, with the population of purebred and crossbred sheep Chios constituting the 97% of farmed sheep on the island. In Cyprus, Chios breed is bred mostly for it’s milk, therefore the amount of milk production is a key determinant of the economic effect of rearing milk producing animals, so the producers main objective is to increase yields. The research to identify genes that affect milk has caused a great interest. From studies it was found that there is single nucleotide polymorphism (SNP) in exon 10 of ACAA2 gene in the 3′ UTR and allele T is associated with increased milk yield (Orford et al. 2012). The objective of this work was to investigate the correlation of ACAA2 gene to the amount of dairy and meat production in Chios sheep in commercial farm. 116 DNA samples were collected and genotyped by sequencing. Examined if the population is in Hardy-Weinberg equilibrium and by Welch's t-test were correlated to ACAA2 gene with milk and meat production. The results did not show correlation to genotypes for milk production. For meat production, results showed correlation in genotypes CC/CT, with other genotypes not presenting correlation. Therefore, for the small number of samples, polymorphism of a base in exon 10 of ACAA2 gene does not seem to affect the milk production and affects the growth of lamb.
Keywords: Sheep industry; Milk production; Meat production